The role of risk attitudes in shaping digital privacy preferences: evidence from a large-scale survey - Jing Chen; Manling Zhang; Mengyao Guo; Ze Gao (Humanities & Social Sciences Communications)
Abstract This paper investigates the relationship between individuals’ heterogeneous risk attitudes and privacy preferences using survey data from 24,899 respondents. It moves beyond demographic factors to examine how risk attitudes, the key psychological parameters in the utility function that determines consumer behaviors, related to consumers’ privacy decisions. Participants indicated their privacy preferences across eight dimensions, including age privacy, marital status privacy, and privacy preferences in the investment and financial obligation realms. We evaluated their risk attitudes through qualitative assessment and quantitative investment loss tolerances, as well as their risk attitudes towards rare and distant events. The study reveals that individuals with higher risk aversion exhibit more significant privacy concerns, especially regarding financial information. Individuals who perceive climate change—a non-immediate and rare risk—as a threat to their lives are also more likely to exhibit heightened concerns about their privacy. In addition, we observe that while these concerns translate into higher non-disclosure actions, the privacy paradox persists regardless of individuals’ risk attitudes. The findings suggest that privacy policies could be more effective through tailored approaches, including customized privacy settings and targeted educational campaigns that account for individual risk aversion.